2005
DOI: 10.1016/s0002-9440(10)62478-9
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation Prevents Alcoholic Liver Injury in Mice through Attenuation of Oxidative Stress

Abstract: Alcoholic liver disease is associated with zinc decrease in the liver. Therefore, we examined whether dietary zinc supplementation could provide protection from alcoholic liver injury. Metallothionein-knockout and wild-type 129/Sv mice were pair-fed an ethanol-containing liquid diet for 12 weeks, and the effects of zinc supplementation on ethanol-induced liver injury were analyzed. Zinc supplementation attenuated ethanol-induced hepatic zinc depletion and liver injury as measured by histopathological and ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 49 publications
11
128
0
1
Order By: Relevance
“…Although there are not any studies on the effectiveness of zinc in spinal cord I/R injuries, it is stated that zinc supplementation causes an increase in the levels of antioxidants such as GSH and GPx. 29 When the XO activities in the spinal tissue were investigated, it was found that these parameters considerably increased especially in the I/R group. However, there was a remarkable decrease in these parameters in groups in which zinc, melatonin and melatonin þ zinc applications were implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are not any studies on the effectiveness of zinc in spinal cord I/R injuries, it is stated that zinc supplementation causes an increase in the levels of antioxidants such as GSH and GPx. 29 When the XO activities in the spinal tissue were investigated, it was found that these parameters considerably increased especially in the I/R group. However, there was a remarkable decrease in these parameters in groups in which zinc, melatonin and melatonin þ zinc applications were implemented.…”
Section: Discussionmentioning
confidence: 99%
“…Zn has catalytic and structural roles in more than 300 metalloenzymes, as well as regulatory roles in diverse cellular processes such as signaling transduction and gene expression (McCall et al, 2000). Many studies have demonstrated that Zn per se functions as antioxidant and also plays an important role in regulation of cellular glutathione (GSH) (Parat et al, 1997;Powell, 2000;Zhou et al, 2005). Although GSH is the most important molecule involved in cellular antioxidant defense, radical scavenging activity of GSH is 300-times lower than that of MT (Thornalley and Vasak, 1985).…”
Section: Effect Of Zn and CD Against Acute Ccl 4 Toxicitymentioning
confidence: 99%
“…Numerous other antioxidants show efficacy in treating fatty liver diseases and include Nacetylcysteine [166], zinc [167,168], silymarin [169], and ursodeoxycholic acid [170], just to name a few. Please refer to the following excellent review articles for additional information on antioxidant therapy for treatment of fatty liver diseases from multiple causes [144,[171][172][173][174].…”
Section: Are Antioxidants Feasible Treatments For Fatty Liver Disease?mentioning
confidence: 99%